Estimating local eradication costs for invasive Miscanthus populations throughout the eastern and midwestern United States. (29th September 2022) - Lowry, Carolyn J.; Matlaga, David P.; West, Natalie M.; Williams, Martin M.; Davis, Adam S.
Abstract: Several Miscanthus species are cultivated in the U.S. Midwest and Northeast, and feral populations can displace the native plant community and potentially negatively affect ecosystem processes. The monetary cost of eradicating feral Miscanthus populations is unknown, but quantifying eradication costs will inform decisions on whether eradication is a feasible goal and should be considered when totaling the economic damage of invasive species. We managed experimental populations of eulaliagrass ( Miscanthus sinensis Andersson) and the giant Miscanthus hybrid ( Miscanthus × giganteus J.M. Greef & Deuter ex Hodkinson & Renvoize) in three floodplain forest and three old field sites in central Illinois with the goal of eradication. We recorded the time invested in eradication efforts and tracked survival of Miscanthus plants over a 5-yr period, then estimated the costs associated with eradicating these Miscanthus populations. Finally, we used these estimates to predict the total monetary costs of eradicating existing M. sinensis populations reported on EDDMapS. Miscanthus populations in the old field sites were harder to eradicate, resulting in an average of 290% greater estimated eradication costs compared with the floodplain forest sites. However, the cost and time needed to eradicate Miscanthus populations were similar between Miscanthus species. On-site eradication costs ranged from $390 to $3, 316 per site (or $1.3 to $11 m −2 ) in the old field sites, compared with only $85 to $547 (or $0.92 to $1.82 m −2 ) to eradicate populations within the floodplain forests, with labor comprising the largest share of these costs. Using our M. sinensis eradication cost estimates in Illinois, we predict that the potential costs to eradicate populations reported on EDDMapS would range from $10 to $37 million, with a median predicted cost of $22 million. The monetary costs of eradicating feral Miscanthus populations should be weighed against the benefits of cultivating these species to provide a comprehensive picture of the relative costs and benefits of adding these species to our landscapes.